Manganese promotion of a Co/SiO2 Fischer-Tropsch catalyst - Mathe, Silethukuthula (Department of Chemical Engineering, 2022)
This study tests the hypothesis that the incorporation of manganese into cobaltbased/silica (SiO2) catalyst influences the activity and selectivity of the FischerTropsch synthesis via the enhancement of CO adsorption and dissociation. The base catalyst is prepared by impregnation (IMPR) of the SiO2 support with cobalt(II) nitrate hexahydrate followed by calcination at 230 °C under a continuous flow of air. This IMPR approach resulted in the successful formation of well-defined and monodisperse cobalt nanoclusters over SiO2 support material. The catalyst precursor containing 22 wt.% Co/SiO2 were doped with different manganese concentrations using strong electrostatic adsorption (SEA) and IMPR approaches. The physico-chemical properties of the catalyst precursors were characterised using ICP-OES, XRD, TEM, STEM-EDS, H2-TPR, TGA, H2 chemisorption and CO-TPD. The catalytic performances of the reduced catalysts in the Fischer-Tropsch synthesis were tested in a fixed bed reactor at 220 °C and 20 barg with (H2/CO)inlet = 2. The incorporation of small amounts of manganese into the Co/SiO2 catalyst precursor, via SEA, resulted in enhanced catalytic activity and this was attributed to the higher degree of cobalt reduction obtained with these materials. However, high manganese contents resulted in decreased catalytic performance, which may be associated with the blockage of catalytically active, cobalt surface sites. There was no evidence of enhanced CO adsorption and dissociation over Co/SiO2 catalyst as a result of the inclusion of selectively adsorbed manganese. Furthermore, the addition of selectively adsorbed manganese on Co/SiO2 catalyst did not significantly change the CH4, C2-4 and C5+ selectivities. The olefin content was the lowest with very small amount of manganese when compared to unpromoted cobalt catalyst, however, a further increase in manganese concentration resulted in an increased olefin content. Lastly, changing the doping method from SEA to IMPR (without pH adjustment) did not significantly change the activity and selectivity of cobalt catalysts. Thus, the change in the method of doping did not influence the activity and selectivity of the cobalt-based catalysts.